Bone regeneration in dehiscence-type defects at non-submerged and submerged chemically modified (SLActives) and conventional SLA titanium implants: an immunohistochemical study in dogs - Frank Schwarz, Martin Sager (Blackwell Synergy, 2008)
Objectives: The aim of the present study was to evaluate bone regeneration in dehiscence-type defects at non-submerged and submerged titanium implants with chemically modified (mod) and conventional sandblasted/acid-etched (SLA) surfaces. Material and Methods: Standardized buccal dehiscence defects were surgically created following implant site preparation in both the upper and lower jaws of 12 beagle dogs. Both types of implants were randomly assigned to either a non-submerged or a submerged healing procedure. After 1, 2, 4, and 8 weeks, dissected blocks were processed for histomorphometrical [e.g. new bone height (NBH), per cent linear fill (PLF), percentage of bone to implant contact (BIC-D), area of new bone fill (BF)] and immunohistochemical analysis. Results: At 8 weeks, non-submerged and submerged SLA implants revealed significantly lower mean NBH (1.1 0.8–1.9 1.2 mm), PLF (27.7 20.3– 46.0 28.5%), BIC-D (26.8 10.4–46.2 16.2%), and BF (1.3 0.9– 3.4 2.8mm2) values than respective modSLA implants [NBH (2.6 0.8– 4.3 0.1 mm), PLF (64.2 19.4–107.2 4.7%), BIC-D (67.5 18.8–82.1 14.8%), BF (2.9 1.0–6.7 1.1mm2)]. Within modSLA groups, significantly highest BF values were observed at submerged implants. Conclusion: It was concluded that (i) modSLA titanium surfaces promoted bone regeneration in acute-type buccal dehiscence defects and (ii) a submerged healing procedure improved the outcome of healing additionally.